PENGGUNAAN COPYWRITING UNTUK MARKETPLACE DI UMKM BINAAN RUMAH BUMN ENDE - Witi, Ferdinandus Lidang; Rawe, Aschari Senjahari; Mude, Anastasia (LPPM Universitas Flores, 2025)
The need for internet technology in Indonesia has increased significantly, which aligns with the growth of MSMEs. This also happens in the Ende Regency. The development of MSMEs in Ende Regency is rising every year. These MSMEs receive a lot of assistance from several institutions such as the Cooperative and MSME Service, Bank NTT and Rumah BUMN Ende. At Rumah BUMN Ende, training activities are always carried out for MSMEs because the goal of this Rumah BUMN is for MSMEs to go digital and online. The digital platforms used are social media and marketplaces. In the course of using this marketplace, it was found that there was still very little application of storytelling and copywriting to carry out promotions. Copywriting is an important promotion activity. The implementation method of this activity includes the preparation stage, the implementation stage and the evaluation stage. The implementation stage is divided into 3 parts, namely theory, practice and discussion. These results show that of the 47 participants who attended, 100% already understood copywriting and were ready to apply it to the marketplace they had. Copywriting training held at Rumah BUMN Ende positively impacts participants' ability to market their products digitally.